Analysis of the Impact of Digital Competency-Based Training and Organizational Culture on Employee Productivity in Industry 4.0 in East Java - Dita Rachmawati; Vincensia Devi Dwi Cahyani (JOURNAL KOPERASI DAN MANAJEMEN, 2026)
Purpose – This study aims to investigate the effects of digital competency-based training (DCBT) and organizational culture on employee productivity in the context of Industry 4.0 in East Java, Indonesia. It specifically examines whether organizational culture, particularly innovation and support, moderates the relationship between DCBT and employee productivity. Design/methodology/approach – This study employed a quantitative research design using structured questionnaires distributed to 350 employees working in manufacturing and technology-intensive firms in East Java, Indonesia. Multiple regression analysis was used to examine the direct effects of DCBT and organizational culture on employee productivity and to test the moderating effect of organizational culture. Findings – The results indicate that DCBT has a significant positive effect on employee productivity (? = 0.452, p < 0.001), while organizational culture, particularly its innovation and support dimensions, also has a significant positive effect (? = 0.387, p < 0.001). Furthermore, organizational culture significantly moderates the relationship between DCBT and employee productivity, with adaptive and learning-oriented cultures strengthening the effectiveness of digital competency-based training. These findings suggest that technical training alone is insufficient to maximize productivity in the Industry 4.0 era and must be supported by an innovative, adaptive, and learning-oriented organizational environment. Research limitations/implications – This study is limited to employees in manufacturing and technology-intensive firms in East Java, which may restrict the generalizability of the findings to other industries or regions. The cross-sectional design also limits the ability to assess the long-term effects of digital competency-based training. Future research could employ longitudinal designs and examine other organizational factors, such as leadership, employee engagement, digital leadership, and technological readiness. Originality/value – This study contributes to the human resource development and Industry 4.0 literature by integrating digital competency-based training and organizational culture into a unified framework for explaining employee productivity. Its originality lies in demonstrating the moderating role of organizational culture in strengthening the effectiveness of digital competency-based training.